Diagnosis dan Tatalaksana HIV grade III dengan TB paru - Benny Syahputra Gumay; Dwiki WIjaya Rahman; Risti Graharti (CV. Jasa Sukses Abadi, 2023)
Human immunodeficiency virus (HIV) is an infection that attacks the immune system, specifically white blood cells called CD4+ cells. HIV continues to be a major global public health problem, claiming 40.1 million lives so far. By 2021, 650,000 people will die from HIV-related causes and 1.5 million people will contract HIV. HIV destroys CD4+ cells, thereby overcoming a person's immunity against opportunistic infections, such as tuberculosis, yeast infections, bacterial infections, and some cancers. Case report of a 29 year old man, came with complaints of shortness of breath since 3 days before entering the hospital. Complaints are accompanied by a long cough, weakness, cold sweats at night, loss of appetite, and weight loss. The serological examination showed HIV reactive results and the chest X-ray showed the impression of active pulmonary TB. The diagnosis established was HIV grade III with clinically diagnosed pulmonary TB, after which the patient was given HIV treatment with co-infected pulmonary TB.